The effect of translocation-induced nuclear reorganization on gene expression - Harewood, Louise; Schütz, Frédéric; Boyle, Shelagh; Perry, Paul; Delorenzi, Mauro; Bickmore, Wendy A.; Reymond, Alexandre

(untitled) (Genome Research, 2010)
Translocations are known to affect the expression of genes at the breakpoints and, in the case of unbalanced translocations, alter the gene copy number. However, a comprehensive understanding of the functional impact of this class of variation is lacking. Here, we have studied the effect of balanced chromosomal rearrangements on gene expression by comparing the transcriptomes of cell lines from controls and individuals with the t(11;22)(q23;q11) translocation. The number of differentially expressed transcripts between translocation-carrying and control cohorts is significantly higher than that observed between control samples alone, suggesting that balanced rearrangements have a greater effect on gene expression than normal variation. Many of the affected genes are located along the length of the derived chromosome 11. We show that this chromosome is concomitantly altered in its spatial organization, occupying a more central position in the nucleus than its nonrearranged counterpart. Derivative 22-mapping chromosome 22 genes, on the other hand, remain in their usual environment. Our results are consistent with recent studies that experimentally altered nuclear organization, and indicated that nuclear position plays a functional role in regulating the expression of some genes in mammalian cells. Our study suggests that chromosomal translocations can result in hitherto unforeseen, large-scale changes in gene expression that are the consequence of alterations in normal chromosome territory positioning. This has consequences for the patterns of gene expression change seen during tumorigenesis-associated genome instability and during the karyotype changes that lead to speciation.